Penggunaan metode permainan dan media loose part untuk meningkatkan kemampuan berhitung siswa kelas 1 sdn ngrambe 1 - Septin Wahyuningrum (Universitas PGRI Madiun, 2026)
Numeracy skill is a fundamental mathematical ability that must be mastered by Grade 1 elementary school students. However, observations at SDN Ngrambe 1 indicated that students' numeracy skills remained low. This was attributed to instruction that was conventional in nature and lacked appeal for the students. This study aimed to improve the numeracy skills of Grade 1 students at SDN Ngrambe 1 through the use of game-based methods and loose parts media. The study employed Classroom Action Research conducted over two cycles. The subjects were Grade 1 students at SDN Ngrambe 1 during the 2025/2026 academic year. Data collection techniques included observation, testing, and documentation, while data analysis involved both quantitative and qualitative descriptive methods. The results showed that the use of game-based methods and loose parts media successfully improved students' numeracy skills. The percentage of student mastery reached 65% in Cycle I and increased to 90% in Cycle II. Based on these results, it can be concluded that game-based methods and loose parts media are effective for improving the numeracy skills of Grade 1 students at SDN Ngrambe 1.